Gender Disparities in Pandemic-Related Strains, Digital Coping Strategies, and Protective Mechanisms Among Rural-to-Urban Migrant Working Adolescents in China - Xinge Jia; Hua Zhong; Qian Wang; Qiaobing Wu (Behavioral Sciences)
The COVID-19 pandemic placed significant strains on daily life, particularly affecting vulnerable groups such as rural-to-urban young migrant workers. Based on General Strain Theory (GST), these pandemic-related strains lead to delinquent copings, including excessive Internet use. However, the association between pandemic-related challenges faced by migrant youth and their digital copings has yet to be investigated. GST also posits that some conditioning factors, such as conventional beliefs, internal resilience and life satisfaction, might serve as protective factors, which can help to alleviate the disruptive consequences of the pandemic-related strains. Utilizing the fourth sweep of International Self-Report Delinquency Survey (ISRD4) in China comprising 769 working migrant adolescents aged 16 to 19, who did not attend high school, the present study examines variations in pandemic-related strains, frequent use of the Internet for gaming and social media, and their associations. In addition, this study investigates the moderating effect of three protective factors: conventional beliefs, internal resilience and life satisfaction. Results indicated that economic strain, information strain and health-related strain significantly influenced digital coping strategies, with notable gender differences. Conventional beliefs served as a significant moderator for males, while life satisfaction played a more significant moderating role for females. Relevant policy implications are then discussed.